Irradiation-responsive polysulfone film as a colorimetric UVA/UVB differentiator - Monteiro, Bernardo (2023)
Funding Information: This work was supported by the Associated Laboratory for Sustainable Chemistry-Clean Processes and Technologies-LAQV, which is financed by national funds from FCT/MEC and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER–007265).This work was also supported by Fundação para a Ciência e a Tecnologia through the contract no IST-ID/077/2018 (Bernardo Monteiro). Cláudia C. L. Pereira thanks Fundação para a Ciência e a Tecnologia, MCTES, for the Norma transitória DL 57/2016 Program Contract. Publisher Copyright: © 2023 The Royal Society of Chemistry.